Enterprise’s business value in economy based on knowledge - Kolesnikova, Irina Iwanowna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
The aim of work is to analyze the difference between the capitalized cost of the enterprise and the value of the assets gives the business value. For the analyzed enterprises in most cases the difference between the market and balance sheet of a single share is a negative value. Thus, the business value is also a negative value. In this connection it is neces[1]sary to create economic, ecological, social-psychological and organization basis of optimization of business cost, to develop the Republic stock exchange. It will promote the increase of competitiveness of Byelorussian enterprises in conformity with innovation receptivity of economic policy.

Celem opracowania jest analiza różnic pomiędzy skapitalizowanymi kosztami przedsiębiorstwa i wartością aktywów, która określa wartość rynkową. Wśród analizowanych przedsiębiorstw, w większości przypadków różnica pomiędzy rynkową a bilansową wartością pojedynczej akcji była ujemna. Stąd, rynkowa wartość jest także ujemna. W związku z tym niezbędne jest tworzenie ekonomicznych, ekologicznych, socjopsychologicznych i organizacyjnych podstaw optymalizacji kosztów przedsięwzięcia, konieczny jest więc rozwój krajowego rynku papierów wartościowych. Takie działania wypromują wzrost konkurencyjności białoruskich przedsiębiorstw w ramach ukierunkowanej innowacyjnie polityki gospodarczej.
Rynkowa wartość przedsiębiorstwa w gospodarce opartej na wiedzy